Search for a light pseudoscalar Higgs boson in the boosted μμττ final state in proton-proton collisions at √s = 13 TeV - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Bergauer Th. Thomas; Zhokin A. S. Aleksandr Sergeevich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2020, 2020)
Title screen